Free versus regulated migration: Comparing the wages of the New Zealand-born, other migrants and the Australia-born workers in Australia - Doan, Tinh; Nghiem, Nhung; Doan, Nhan (My University, 2022)
New Zealanders can cross borders freely, work and live in Australia indefinitely thanks to the Trans-Tasman Travel Agreement. This paper uses a recently developed decomposition method to decompose the weekly wage gap at various quantiles on the wage distribution between New Zealand-born (NZ-born) and Australian-born workers, and between NZ-born workers, migrants from other English speaking countries (OESC), and from non-English speaking countries (NESC) to determine how free and regulated migration influences migrants’ performance in the Australian labour market. We found that NZ-born workers earned higher weekly wages than both Australian-born and NESC workers but earned lower wages than OESC migrants. Differences in endowment were primarily responsible for the wage gaps between NZ-born and Australian-born workers and between NZ-born and OESC migrants. However, differences in returns to worker and job characteristics are mainly responsible for the wage gap between NZ-born and NESC migrants.
International Migration
Keywords: Income, wealth and finances; Labour market; Migration and settlement